KETERWAKILAN PEREMPUAN DI DPRD KOTA MAKASSAR PERSPEKTIF SIYASAH DUSTURIYAH - Fadila S, Nur Azzah; Alimuddin, Alimuddin (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
The position of women in politics seems to play only a secondary role, even though regulatively, women have been given privileges through the arrangement of a 30% quota for the nomination of legislators. This study aims to find out how the representation of women in the Dewan Perwakilan Rakyat Daerah (DPRD) of Makassar City. This research is a field qualitative research, with a statutory and normative approach to syar’i. Based on the results of the 2019 General Election, the level of women’s representation in the Makassar City DPRD reached 26% (13 people) out of a total of 50 people in the number of members of the Makassar City DPRD. Cumulatively, this figure has not met the 30% quota mandated by law. This is due to several factors such as the system of regeneration of political parties, women’s interest in getting involved, family support, and the high cost of politics. From the perspective of siyasah dusturiyah, the arrangement regarding the 30% quota for women in the nomination of legislators should not be interpreted textually according to the text of the Qur’an or hadith, but should be based on leadership ability.